A Stacked Planar Antenna with Switchable Small Grid Pixel Structure for Directive High Beam Steering Broadside Radiation - Subramaniam, Devakumaran; Jusoh, Muzammil; Sabapathy, Thennarasan; Nasrun Osman, Mohamed; Ramlee Kamarudin, Muhammad; Tarmizi Ali, Mohd; Najib Mohd Yasin, Mohd; Ali, Azuwa; A. Majid, H; Rahim, Robbi (International Journal of Engineering and Technology, 2018)
A radiation pattern of a reconfigurable pixel structure antenna that operates in three steerable beam directions of -40Âº, 0Âº, 40Âº is presented. The proposed antenna consists of a circular driven structure on the bottom layer with a pixel structure placed in the top layer. The pixel structures of small square-shaped metallic patches are used to provide beam steering reconfiguration capabilities to the antenna. The adjacent pixels are connected by PIN diode switches with ON/OFF status to change the electrical geometry of the pixel surface, which changes the current distribution on the antenna, thus provides reconfigurability in beam steering direction. The proposed antenna operates at 9.5GHz frequency for X-Band radar application. This antenna is capable to achieve a tolerable return loss of less than -10dB with an average gain of 8 dBi at all desired angles.Â